Depression and academic engagement among college students: the role of sense of security and psychological impact of COVID-19 - Tang, Yuxi; He, Weiguang (Frontiers in Public Health, 2023)
Background: The negative consequences of depression in college students have garnered global attention, especially in relation to academic achievement during the COVID-19 pandemic, which need critical assessment. Aim: This study investigated whether a sense of security mediated the relationship between depression and academic engagement among college students during the pandemic and whether the moderating psychological impact of COVID-19 has a moderating effect on this relationship. Methods: In this cross-sectional study, we recruited 466 college students from 30 provincial-level administrative regions in China via the Internet and used established scales to measure depression, academic engagement, a sense of security, and the psychological impact of COVID-19. The mediating and moderating effects were tested using the bootstrap method. Results: Depression was found to negatively influence academic engagement, with a sense of security partially mediating this relationship. Moreover, the psychological impact of COVID-19 was shown to have a moderating effect on this mediating process. Conclusion: This study could aid in crafting pertinent strategies to mitigate the adverse effects of depression on learning amid unexpected public health crises and foster better mental health among college students.